017 PROVE study 506: perampanel in real-world clinical care of patients based on seizure type. Issue 6 (27th May 2022) - Wheless, James; Patten, Anna; Ngo, Leock Y; Salah, Alejandro; Malhotra, Manoj
Abstract : Background: PROVE (NCT03208660 ) was a retrospective, non-interventional Phase IV study of perampanel during real-world clinical care of patients with epilepsy; we report the efficacy and safety of perampanel in PROVE. Methods: Data from patients initiating perampanel after 01-Jan-2014 were included. Endpoints included retention rate at 3/6/12/18/24 months (primary), efficacy and safety (secondary). Outcomes were strati- fied by baseline seizure type: focal-onset seizures (FOS) only; generalised seizures only; generalised tonic- clonic seizures (GTCS) only; myoclonic; absence. Patients with FOS and generalised seizures (n=718) were excluded. Results: In the Safety Analysis Set (n=1703), 24-month retention rates were: 48.1% (FOS only, n=164/341); 47.8% (generalised only, n=120/251); 42.9% (GTCS only, n=27/63); 50.3% (myoclonic, n=100/199); 47.7% (absence, n=84/176). Of 51 patients with seizure data at Months 22–24, median reductions in total seizure frequency/28 days were: 75.0% (FOS only, n=20); 91.6% (generalised only, n=10); 40.0% (GTCS only, n=3); 70.0% (myoclonic, n=7); 100.0% (absence, n=4). Treatment-emergent adverse events occurred in 231/545 (42.4%; FOS only), 185/440 (42.0%; generalised only), 50/110 (45.5%; GTCS only), 117/328 (35.7%; myoclonic) and 154/301 (51.2%; absence) patients; most common were dizziness and aggression. Conclusion: Perampanel retention rates and safety were generally similar across seizure types. Seizure frequency reductions were observed across subgroups. Funding.Eisai Inc. stella_ngo@eisai.com